Bioprospecting of South African Plants as a Unique Resource for Bioactive Endophytic Microbes - Abdalla, Muna Ali; McGaw, Lyndy J. (Frontiers in Pharmacology, 2018)
South Africa has a long history and strong belief in traditional herbal medicines. Using ethnobotanical knowledge as a lead, a large number of South African medicinal plants have been discovered to possess a wide spectrum of pharmacological properties. In this review, bioprospecting of endophytes is highlighted by following the advantages of the ethnomedicinal approach together with identifying unique medicinal plants where biological activity may be due to endophytes. This review focuses on the current status of South African medicinal plants to motivate the research community to harness the benefits of ethnobotanical knowledge to investigate the presence of endophytic microbes from the most potent South African medicinal plants. The potential chemical diversity and subsequent putative medicinal value of endophytes is deserving of further research. A timely and comprehensive review of literature on recently isolated endophytes and their metabolites was conducted. Worldwide literature from the last two years demonstrating the importance of ethnobotanical knowledge as a useful approach to discover endophytic microbes was documented. Information was obtained from scientific databases such as Pubmed, Scopus, Scirus, Google Scholar, Dictionary of Natural Products, Chemical Abstracts Services, official websites and scientific databases on ethnomedicines. Primary sources such as books, reports, dissertations and thesises were accessed where available. Recently published information on isolated endophytes with promising bioactivity and their bioactive natural products worldwide (2015-2017) was summarized. The potential value of South African medicinal plants as sources of endophytes is discussed. The insights provided through this study indicate that medicinal plants in South Africa are highly under-investigated sources of potentially useful endophytic microbes. New approaches may be used by medicinal plant scientists for further exploration of natural products from endophytic fungi and bacteria in southern Africa.